Abnormalities in the Fractional Amplitude of Low-Frequency Fluctuation and Functional Connectivity in Parkinson's Disease With Excessive Daytime Sleepiness - Zi, Yuheng; Cai, Sainan; Tan, Changlian; Wang, Tianyu; Shen, Qin; Liu, Qinru; Wang, Min; Li, Junli; Zhang, Lin; Zhou, Fan; Song, Chendie; Yuan, Jiaying; et al. (Frontiers in Aging Neuroscience, 2022)
Background: Excessive daytime sleepiness (EDS) is one of the most important non-motor symptoms of Parkinson's disease (PD), and its neuropathologic basis is still unclear. Objective: This study investigated the changes of neuronal activity in PD patients with EDS (PD-EDS) in the resting state. Methods: Forty-three PD patients were recruited and divided into the PD-EDS group (n=21) and PD-NEDS group (PD patients without excessive daytime sleepiness, n=22) according to the Epworth sleepiness scale (ESS) scores. Patients in both groups received resting-state functional magnetic resonance imaging (rs-fMRI). The differences in fractional amplitude of low-frequency fluctuation (fALFF) between the two groups, correlations between fALFF and ESS, and functional connection (FC) between the brain regions with different fALFF values and the whole brain were analyzed. Results: PD-EDS patients exhibited a decreased fALFF in the Cingulum-Ant-R, but an increased fALFF in the Putamen-R and Thalamus-L when compared with PD-NEDS patients; an increased functional connectivity between these three seed regions with different fALFF values and the right medial frontal gyrus, bilateral superior temporal gyrus, left insular, and right precuneus was observed (p<0.05), but a deceased functional connectivity between these three seed regions and the right cerebellum anterior lobe/right brainstem, right middle temporal gyrus and inferior temporal gyrus, right hippocampus/parahippocampal gyrus, right medial cingulate gyrus and bilateral middle occipital gyrus was observed (p<0.05). The value of fALFF was negatively correlated with the ESS score in the Cingulum-Ant-R, but positively correlated with the ESS score in the Putamen-R and Thalamus-L. Conclusions: EDS in PD patients may be associated with changes in brain neuron activity and functional connectivity.